IMPLEMENTASI FRAMEWORK PADA PEMERIKSAAN ANTIBODI COVID 19 DI UNIT PELAKSANA TEKNIS LABORATORIUM KESEHATAN KOTA BANDUNG - Suyarta Efrida Pakpahan; Raudatul Jannah; Barianti (Jurnal Health Sains, 2022)
Examination of antibodies to Severe Acute Respiratory Syndrome using point-of-care immunodiagnostics has a sensitivity and specificity value of less than 95%. This study aims to determine the implementation of the framework for the examination of Covid-19 antibodies in the Technical Implementation Unit of the Bandung City Health Laboratory. Research method: This study uses a descriptive approach, explanatory, cross sectional research time with experimental quantitative methods. From the implementation of the framework for the examination of Covid-19 antibodies, it is well illustrated, indicated by high validity with a value of 0.830 > 0.30 for GB reagent, 0.983 > 0.30 and high reliability with a value of 0.860 > 0.50 for GB reagent, 0.989 > 0, 50 for the four reagents used in the Technical Implementation Unit of the Bandung City Health Laboratory, namely Bio reagent, Zy reagent, Abbt reagent. The results of the Framework Implementation on the Antibody Examination of Covid 19 for 3 reagents are not good and 4 reagents can be said to have good reliability and high reagent reliability Coronavirus Disease 2019 (Covid 19) is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a new type of coronavirus that has never been previously identified in humans. There are at least two types of coronavirus that are known to cause diseases that can cause severe symptoms such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS).